Monument to Caroline Dickson - Yaron Perry:::Creator::::::::::::
A Monument to Caroline Samueletta Dickson (1847-1932). Other sides of the gravestone give details of the family's travails in Palestine. Caroline, age 11, was present when Friedrich Steinbeck (previously Grosssteinbeck, her brother-in-law) was killed, Mary E. Dickson Steinbeck (her sister) and Sarah Dickson (her mother) were raped, and Walter Dickson (her father) was beaten at their home near Jaffa, Israel. The family left soon after for Massachusetts. Caroline and Mary were the sisters of Almira Dickson who married John Adolph Grosssteinbeck. Almira and John Adolph are John Steinbeck's paternal grandparents. Digital copy only. No hard copy.